An Overview of Methods Used in the Determination of Soil Hydraulic Conductivity - Musa, J.J.; Gupa, Y.U. (Al-Hikmah Journal of Pure and Applied Sciences (AJPAS), 2019)
Hydraulic conductivity is one of the most important parameter for flow and transport related phenomena in soil. There is concern arising from the suitability, efficiency and ease of the different measuring methods under different conditions. The various methods of determining hydraulic conductivity include field, laboratory and correlation methods each with individual merits and demerits. Although selection of a specific method for a particular application will depend on the objectives to be achieved, most researchers prefer direct measurement of soil hydraulic conductivity. The estimation of soil hydraulic conductivity using correlation method depends on the local soil maps, soil particle size distribution, organic matter content and bulk density. Field methods are usually more expensive than laboratory methods. Consequently, when the question of cost becomes decisive, or when actual representation of field conditions is not of fundamental importance and in-situ hydraulic conductivity is not available, laboratory methods may be used to determine the saturated hydraulic conductivity K. Overall, this review explains the various methods that can be used to determine hydraulic conductivity in-situ or within the laboratory.